Java 2 : The Complete Reference - Naughton, Patrick and Schildt, Herbert (Berlekey Osborne/McGraw-Hill, 1999)
This text gives coverage of the Java language and new JDK for all levels of programmers. The book reflects changes from 1.1 to 1.2 - servlets, swing component set, utility class and Java 2-D API. Complete source codes online for interactive client/server application are also presented.
Keywords: Java (Computer program language) -- Internet programming